Identification of RCC1–LCK as a novel fusion gene in pediatric erythroid sarcoma. Issue 9 (30th June 2022) - Oya, Satoru; Osone, Shinya; Yoshida, Masanori; Nishimoto, Sota; Taura, Yoshihiro; Yoshida, Hideki; Miyachi, Mitsuru; Inaba, Tohru; Konishi, Eiichi; Kato, Motohiro; Imamura, Toshihiko; Iehara, Tomoko
Abstract: Erythroid sarcoma is a very rare subtype of myeloid sarcoma with undetermined biological features. Here, we present an infant with a multifocal erythroid sarcoma, diagnosed because the tumor cells were positive for glycophorin A. After acute myeloid leukemia‐oriented chemotherapy and surgical resection followed by cord blood transplantation, he has successfully maintained complete remission without any late effects. Total transcriptome analysis of the tumor identified a novel fusion gene, RCC1–LCK, and high LCK expression levels, suggesting that LCK overexpression was involved in leukemogenesis in this case.